Use of Green Chemistry for Amputation of Chromium Ions from Wastewater by Alkali-Treated Composts of Fruit Peels in Economical Way - Shoomaila Latif; Rabia Rehman; Muhammad Imran; Uzma Hira; Shahid Iqbal; Mehwish Akram; Liviu Mitu; Reem I Alsantali; Zahrah T. Al-thagafi (Journal of Chemistry)
In this work, removal of chromium (VI) using alkali-treated composted peels of lemon (Citrus limonum), mango (Mangifera indica), water melon (Citrullus lanatus), and melon (Cucumis melo) has been studied in batch mode. Physico-chemical characteristics of each sorbent material were determined together with their subsequent characterization by scanning electron microscopic, FTIR, and TGA. The selected sorbent materials were chemically modified using nitric acid and sodium hydroxide solutions. Adsorption efficacy of the selected sorbent materials for Cr (VI) was investigated by optimizing different parameters. The most favorable conditions were as follows: adsorbent dosage = 1.2 g/50mL, pH = 4.0, agitation speed = 170 rpm, 60 minutes = contact time, and temperature = 313°K. Base-treated adsorbents were found to be better adsorbents as compared to the acid treated form which in turn are better than raw adsorbents (adsorbents without chemical modification). Overall, the chosen sorbents removed Cr (VI) in the range of 53.62–96%, whereas the maximum sorption is with base-treated water melon peels (BWMP), that is, 95.98%. The kinetic studies discovered that the results fitted with pseudo-second-order model. Thermodynamic parameters also support that under optimal conditions, all the selected sorbents specifically base-treated sorbents are good enough for the elimination of Cr (VI) ions in an eco-friendly way.